Basilar Invagination in a Cat with Incomplete Ossification of the Atlas Treated by C1-C2 Arthrodesis - Fontalba-Navas, Jose Luis; Rodríguez-Gómez, Victoria; Calvo, Ignacio; Mateo-Pampliega, Isidro (VCOT Open, 2022)
Basilar invagination is a poorly described condition in veterinary medicine where the tip of the odontoid process projects into a normal foramen magnum. This report describes the clinical, radiological, and surgical treatment of a basilar invagination associated with instability of the atlantoaxial joint due to an incomplete ossification of the atlas in a cat. At presentation, the clinical signs included obtundation and non-ambulatory tetraparesis with postural reaction deficits in hindlimbs and left forelimb. Radiographic examination revealed cranial displacement of the axis with the dens impinging the basioccipital bone, and computed tomography confirmed the impaction of the axis on the atlas due to an incomplete ossification of the left half of the neural arch with the intercentrum. Magnetic resonance imaging confirmed severe spinal cord compression and myelopathy at this level. The cat underwent surgery for atlantoaxial arthrodesis using a ventral approach to C1-C2. Recovery after surgery was uneventful. Follow-up a year after surgery finds the cat free of neurological signs. An incomplete ossification of the atlas can lead to atlantoaxial instability and basilar invagination in the cat. Diagnosis can be made based on its radiological characteristics, the cranial displacement of the odontoid process in contact with the basioccipital bone being its main feature. This case was successfully treated by atlantoaxial arthrodesis.
Keywords: cat; ossification defects; feline occipitoatlantoaxial malformations; atlantoaxial arthrodesis